2018
DOI: 10.1161/jaha.117.008250
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnic and Sex Differences in the Association of Atherosclerotic Cardiovascular Disease Risk and Healthy Lifestyle Behaviors

Abstract: BackgroundLifestyle behaviors influence atherosclerotic cardiovascular disease (ASCVD) risk. We examined race and sex differences in the association of ASCVD risk with obesity and lifestyle behaviors.Methods and ResultsWe used multivariable logistic regression to examine the association of race/ethnicity and sex with obesity and lifestyle behaviors among 12 351 adults in the National Health and Nutrition Examination Surveys cycles 2005 to 2014. Ten‐year ASCVD risk was estimated using the 2013 American College … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…A recent study also reported decreased CSF t-tau and p-tau 181 in Blacks compared to Whites (Morris et al, 2019). These racial neurological disparities have been attributed to the association of Black racial identity with lifestyle behaviors across the life course known to influence cognitive aging (e.g., poor diet, sedentary behaviors) (Morris et al, 2018), cardiovascular disease (CVD) (Newman et al, 2005;Jackson et al, 2013;Benjamin et al, 2019), genetics (e.g., APOEε4 or ABCA7 status) (Reitz et al, 2013;Graff-Radford et al, 2016;Rajan et al, 2019), socioeconomic status (Zahodne et al, 2017), and other factors (Barnes and Bennett, 2014;Zahodne et al, 2017;Brewster et al, 2018). Many of these factors associated with racial identity may influence both clinical and neuropathological outcomes, whereas others (e.g., socioeconomic status) might have more specific impact on clinical function (e.g., neuropsychological test scores, dementia risk).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study also reported decreased CSF t-tau and p-tau 181 in Blacks compared to Whites (Morris et al, 2019). These racial neurological disparities have been attributed to the association of Black racial identity with lifestyle behaviors across the life course known to influence cognitive aging (e.g., poor diet, sedentary behaviors) (Morris et al, 2018), cardiovascular disease (CVD) (Newman et al, 2005;Jackson et al, 2013;Benjamin et al, 2019), genetics (e.g., APOEε4 or ABCA7 status) (Reitz et al, 2013;Graff-Radford et al, 2016;Rajan et al, 2019), socioeconomic status (Zahodne et al, 2017), and other factors (Barnes and Bennett, 2014;Zahodne et al, 2017;Brewster et al, 2018). Many of these factors associated with racial identity may influence both clinical and neuropathological outcomes, whereas others (e.g., socioeconomic status) might have more specific impact on clinical function (e.g., neuropsychological test scores, dementia risk).…”
Section: Introductionmentioning
confidence: 96%
“…Autopsy studies also link Black racial identity with increased risk for neuropathologic changes of AD and related diseases, including cerebrovascular disease (Graff-Radford et al, 2016;Filshtein et al, 2019). Although, some studies have failed to find an association between Black racial identity and AD pathologic changes (Riudavets et al, 2006;Wilkins et al, 2006;Morris et al, 2018) and risk for dementia (Fillenbaum et al, 1998). A recent study also reported decreased CSF t-tau and p-tau 181 in Blacks compared to Whites (Morris et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…1). Compared with excluded patients, included patients had longer duration of DM(96 vs 84 About 75.2% patients were at high risk of 10-year ASCVD event, which was defined as 10-year ASCVD risk ≥ 7.5% [19]. Among group CKD1, 2, 3 and 4 stage, 27.6%, 22.2%, 28.2% and 15.4% patients had 10-year ASCVD risk ≥ 7.5% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…54 A survey conducted to assess the 10-year risk of atherosclerotic CVD noted the highest risk in Black and Hispanic groups compared to other ethnic and racial groups. 55 The high rates of immune suppression in these groups predispose them to an increased inflammatory risk and CVD. 31…”
Section: Are There Disparities In Care For the Immunocompromised?mentioning
confidence: 99%